Biotransformation of 5-en-3β-ol steroids by Mucor circinelloides lusitanicus. Issue 3 (3rd May 2016) - Shan, Lihong; Jiao, Kai; Yin, Minghui; Huang, Jiajia; Chen, Yanjie; Qin, Shangshang; Liu, Hongmin
Abstract: In this work, we report the mode of biotransformation of 5-en-3β-ol steroids using Mucor circinelloides lusitanicus for the first time. Here, we selected seven 5-en-3β-ol steroids as substrates. The main characteristic of the fungus was to introduce a 7α-hydroxyl group into substrates1 --5 . With substrate2, 3β, 7α, 11α-trihydroxypregna-5-en-20-one (2b ) was obtained as the final product in good yield (46.4%). All the metabolites were determined by infrared spectra, high-resolution mass spectrometry, proton nuclear magnetic resonance, and carbon-13 nuclear magnetic resonance.